Polyethylene Terephthalate Wastes as a Partial Replacement for Fine Aggregates in Concrete Mix, Case of Jimma Town, South West Ethiopia - Temesgen Abeto Amibo; Abreham Bekele Bayu; Desalegn Abdissa Akuma (Program Pascasarjana Universitas Sriwijaya, 2021)
In this research Concrete mix designs were prepared according to the DOE method and a total of 6 mixes with 72 samples prepared to consist of concrete grade C-25. The test samples were produced with the percentage of substitution for the fine aggregate by 1, 2, 3, 4, and 5% of PET plastic waste aggregate. Moreover, a control mix without replacement for the fine aggregate was used to have a relative analysis. The prepared samples consist of concrete cubes, cylinders, and beams. Furthermore, laboratory experiments were carried out for the prepared concrete test samples. The lists of experiments conducted were; material property, slump, unit weight, compressive strength, splitting tensile strength, and flexural strength tests. The test results were analyzed and compared with the respective conventional concrete characteristics and show that there was a slight increase in compressive strength of the concrete up to 3% replacement and reduction in compressive strength increases beyond 3% replacement due to the replacement of PET aggregates. Also like compressive strength there was an increase of tensile strength recorded with increasing PET bottle aggregate content up to 3% replacement. But more than 3% substitution of fine aggregate with PET bottle fiber results in a reduction in tensile strength, flexural strength. This test result shows that as it is possible to use PET bottles in concrete production as a partial substitution for fine aggregates not more than 3% replacement.